Prevalence and Risk Factors of Chlamydia trachomatis Cervicitis in Pregnant Women at the Genital Tract Infection in Obstetrics Unit Care at Botucatu Medical School, São Paulo State University - UNESP, Brazil - Ramos, Bruna R.; Polettini, Jossimara; Marcolino, Larissa D.; Vieira, Eliane P.; Marques, Mariângela Esther Alencar [UNESP]; Tristao, Andrea R.; Nunes, Helio R.; Rudge, Marilza Vieira Cunha [UNESP]; Silva, Marcia Guimarães da [UNESP] (Lippincott Williams & Wilkins, 2011)
Objective. To evaluate the prevalence of and risk factors for Chlamydia trachomatis cervicitis in pregnant women seen at the Genital Tract Infection in Obstetrics Unit Care in Botucatu Medical School, São Paulo State University - UNESP.Materials and Methods. Between June 2006 and February 2008, 101 pregnant women were included in this study. During the gynecologic examination, cervical secretions were collected using cytobrush Plus GT (CooperSurgical Inc) to assess C. trachomatis using polymerase chain reaction. Vaginal flora were examined by Gram stain, and socio-demographic data were extracted from medical records.Results. of the 101 patients, 26 (25.7%) were positive for C. trachomatis. The median age of the infected group was 24 years (range = 13-40 y), and 48.5% of them had abnormal vaginal flora. The presence of chlamydial infection was associated with smoking (odds ratio [OR] = 2.67, 95% confidence interval [CI] = 1.01-7.19), residing in a city with fewer than 100,000 inhabitants (OR = 2.86, 95% CI = 1.03-7.94), presence of condyloma acuminatum (p = .03), and presence of discreet inflammation on Pap smear (p = .02).Conclusions. The prevalence of C. trachomatis is high in pregnant women seen at the Genital Infection Unit Care, UNESP, and is related to many risk factors. Therefore, its screening is extremely important in reducing obstetrical and neonatal complications.
Keywords: pregnancy; Chlamydia trachomatis; risk factors; prevalence